2020
DOI: 10.1021/acsomega.0c01757
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Distribution of Cu and Pd Species in CuPd/TiO2–Na Bimetallic Catalysts for Glycerol Hydrodeoxygenation

Abstract: We demonstrated recently that CuPd/TiO 2 –Na bimetallic catalysts synthesized by sequential wet impregnation are active, selective, and stable for the hydrodeoxygenation (HDO) of glycerol into propylene glycol at low H 2 pressure. The present study reports on the nature and distribution of Cu and Pd surface species in CuPd/TiO 2 –Na bimetallic catalysts using different scanning transmission electron microscopy techniques that supply cluster-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…We also demonstrated that the high selectivity to 1,2-PDO of the bimetallic catalysts synthesized is due to the formation of CuPd alloy nanoparticles with sizes smaller than 6–7 nm with their surface enriched with Cu and basically made up of Cu 0 -Pd 0 and Cu 1+ -Pd 0 . 15 However, according to our experimental observations and literature data, obtaining 1,2-PDO from glycerol is not an elementary reaction with 1,2-PDO as the only product formed in the reaction. 9 , 14 20 Thus, depending on the reaction conditions, different intermediates and/or side products could affect the kinetics of the reaction and the selectivity to 1,2-PDO.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…We also demonstrated that the high selectivity to 1,2-PDO of the bimetallic catalysts synthesized is due to the formation of CuPd alloy nanoparticles with sizes smaller than 6–7 nm with their surface enriched with Cu and basically made up of Cu 0 -Pd 0 and Cu 1+ -Pd 0 . 15 However, according to our experimental observations and literature data, obtaining 1,2-PDO from glycerol is not an elementary reaction with 1,2-PDO as the only product formed in the reaction. 9 , 14 20 Thus, depending on the reaction conditions, different intermediates and/or side products could affect the kinetics of the reaction and the selectivity to 1,2-PDO.…”
Section: Introductionsupporting
confidence: 66%
“…We also demonstrated that the high selectivity to 1,2-PDO of the bimetallic catalysts synthesized is due to the formation of CuPd alloy nanoparticles with sizes smaller than 6–7 nm with their surface enriched with Cu and basically made up of Cu 0 -Pd 0 and Cu 1+ -Pd 0 . However, according to our experimental observations and literature data, obtaining 1,2-PDO from glycerol is not an elementary reaction with 1,2-PDO as the only product formed in the reaction. , Thus, depending on the reaction conditions, different intermediates and/or side products could affect the kinetics of the reaction and the selectivity to 1,2-PDO. Nevertheless, to use our catalyst in a specific industrial application for the production of 1,2-PDO from glycerol, it is necessary to understand the reaction mechanism and to know some kinetic models; moreover, to the best of our knowledge, these aspects have not been discussed in the previous studies.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Xia et al reported that by adding 1.3 wt% Pd to a Cu/MgO/Al 2 O 3 catalyst, the glycerol conversion can be increased from 56.7% using an unpromoted catalyst to 79.6% at 2 MPa hydrogen pressure [21]. Ardila et al investigated the synergetic effect of a Cu-Pd catalyst (5 wt% each) supported on Na-treated TiO 2 ; the experimental results suggested that under a low hydrogen pressure (0.7 MPa) the glycerol conversion and 1,2-PD selectivity were all significantly higher when using the supported bimetallic catalyst than when using any supported monometallic (Pd or Cu) catalyst [22,23]. Nevertheless, most of the works focused on the improvement of glycerol conversion and 1,2-PD selectivity by addition of Pd; the kinetics of the promoting effect of Pd have not been clearly identified on the elementary reactions of the process, so that the promoting effect of Pd cannot be mechanistically understood.…”
Section: Introductionmentioning
confidence: 99%